2015
DOI: 10.1016/j.solener.2015.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Solar electricity via an Air Brayton cycle with an integrated two-step thermochemical cycle for heat storage based on Co3O4/CoO redox reactions: Thermodynamic analysis

Abstract: Solar electricity production is considered in an Air Brayton cycle with an integrated two-step thermochemical cycle for heat storage based on Co 3 O 4 /CoO redox reactions. The two steps of the heat storage cycle are encompassed by (1) the high-temperature thermolysis of Co 3 O 4 to CoO and O 2 under vacuum pressure utilizing concentrated solar irradiation for process heat; and (2) the highly exothermic re-oxidation of CoO with O 2 at elevated pressures, resulting in Co 3 O 4 and providing the heat input to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…In a previous work, a thermodynamic analysis of a twostep solar thermochemical cycle for heat storage was performed with integration into an Air Brayton cycle (Schrader et al, 2015). The first step of the cycle is the endothermic thermolysis of Co 3 O 4 driven by concentrated solar irradiation, represented as:…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work, a thermodynamic analysis of a twostep solar thermochemical cycle for heat storage was performed with integration into an Air Brayton cycle (Schrader et al, 2015). The first step of the cycle is the endothermic thermolysis of Co 3 O 4 driven by concentrated solar irradiation, represented as:…”
Section: Introductionmentioning
confidence: 99%
“…Schrader et al [5] suggested a similar concept for thermochemical energy storage, where cobalt oxide is applied under pressurized conditions in a closed system. In addition, the utilization of particles as heat transfer and thermal storage material has been also investigated for sensible energy storage [6][7][8]. Owing to the high temperature level in the solar receiver, it is crucial to extract both the thermochemical energy and inherent sensible energy of the metal-oxide particles in the heat extraction reactor to enhance the total energy density and system efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Since oxygen from ambient air can be used as the reaction gas for a thermochemical reaction, no separate gaseous storage is necessary. The concept of two interconnected reactors for continuous charging and discharging is presented by Schrader et al [28] with CoO as thermochemical storage material and heat transfer medium. A solar reactor for reduction and an oxidation reactor are combined with cold and hot storage tanks to feed an air Brayton cycle.…”
Section: Introductionmentioning
confidence: 99%